Acetylation of Lysine 243 Inhibits the oriC Binding Ability of DnaA in Escherichia coli - Li, Shuxian; Zhang, Qiufen; Xu, Zhihong; Yao, Yu-Feng (Frontiers in Microbiology, 2017)
DNA replication initiation is a central event in the cell cycle, and it is strictly controlled by multiple regulatory mechanisms. Our previous work showed that acetylation of residue lysine (K) 178 prevents DnaA from binding to ATP, which leads to the inhibition of DNA replication initiation. Here, we show that another residue, K243, is critical for DnaA full activity in vivo. K243 can be acetylated, and its acetylation level varies with cell growth. A homogeneous, recombinant DnaA that contains Nε-acetyllysine at K243 (K243Ac) retained its ATP/ADP binding ability, but showed decreased binding activity to the oriC region. A DNase Ι footprinting assay showed that DnaA K243Ac failed to recognize DnaA boxes I3, C1, and C3, and, thus, it formed an incomplete initiation complex with oriC. Finally, we found that acetyl phosphate and the deacetylase CobB can regulate the acetylation level of K243 in vivo. These findings suggest that DnaA K243 acetylation disturbs its binding to low-affinity DnaA boxes, and they provide new insights into the regulatory mechanisms of DNA replication initiation.